Head Lice at School: Traditional Medicine and Community Engagement (Mary Ann Liebert, 2021)
Purpose: The prevalence of head lice in poor rural communities and urban slums is estimated to be between 28% and 43% in Brazil, respectively. Children are among the most affected, often in clusters within schools. We launched a program intending to tackle the social stigma associated with head lice using scientific information and a local traditional remedy as a way to lower the prevalence of head lice in a low-resource community. Methods: A program involving the entire school community and the teachers addressed how to treat head lice and avoid new infestations. An affordable solution widely used in traditional Brazilian medicine was provided for the ones infested. Evaluation of the outcome was based on direct observation and was designed as a satisfaction survey. The study complied with the criteria for Standards for Reporting Qualitative Research (SRQR). Results: Two hundred and eighty participants, including parents and siblings of the school children, took part in the program. Among them, 24% (N=67) had head lice, with girls representing 85% of cases; 74.7% of participants infested with head lice were between 4 and 10 years old; 55.2% (N=37) of participants infested showed no signs of nits or adult lice after the program. Conclusions: This experience suggests that the use of playful activities associated with a well-known and accessible local product to treat head lice in low-income families gathered a high degree of community adherence and may be an important tool in overcoming health inequalities.